Stationary Consistent Equilibrium Coalition Structures Constitute the Recursive Core - László Á. Kóczy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
We study coalitional games where the coalitional payoffs depend on the entire coalition structure. We introduce a noncooperative, sequential coalition formation model and show that the set of equilibrium outcomes coincides with the recursive core, a generalisation of the core to such games. In order to extend past results limited to totally recursive-balanced partition function form games we introduce subgame-consistency that requires perfectness in relevant subgames only, while some unreached subgames are ignored. Due to the externalities, the profitability of deviations depends on the partition formed by the remaining players: the stability of core payoff configurations is ensured by a combination of the pessimism of players going for certain profits only and the assumption that players base their stationary strategies on a made-up history punishing some of the possible deviators - and getting this sometimes right.
Keywords: C71; C72; 330; partition function; externalities; implementation; recursive core; stationary perfect equilibrium; time consistent equilibrium; Koalition; Spieltheorie; Core